Vitamin D and cardiovascular disease prevention - Pilz, Stefan; Verheyen, Nicolas; Grübler, Martin R.; Tomaschitz, Andreas; März, Winfried (Nature reviews. Cardiology, 2016)
Vitamin D is a precursor of the steroid hormone calcitriol that is crucial for bone and mineral metabolism. Both the high prevalence of vitamin D deficiency in the general population and the identification of the vitamin D receptor in the heart and blood vessels raised interest in the potential cardiovascular effects of vitamin D. Experimental studies have demonstrated various cardiovascular protective actions of vitamin D, but vitamin D intoxication in animals is known to induce vascular calcification. In meta-analyses of epidemiological studies, vitamin D deficiency is associated with an increased cardiovascular risk. Findings from Mendelian randomization studies and randomized, controlled trials (RCTs) do not indicate significant effects of a general vitamin D supplementation on cardiovascular outcomes. Previous RCTs, however, were not adequately designed to address extraskeletal events, and did not focus on vitamin D-deficient individuals. Therefore, currently available evidence does not support cardiovascular benefits or harms of vitamin D supplementation with the commonly used doses, and whether vitamin D has cardiovascular effects in individuals with overt vitamin D deficiency remains to be evaluated. Here, we provide an update on clinical studies on vitamin D and cardiovascular risk, discuss ongoing vitamin D research, and consider the management of vitamin D deficiency from a cardiovascular health perspective.
Gesehen am 09.07.2019